Gestational low-protein intake enhances whole-kidney MIR-192 and MIR-200 family expression and epithelial-to-mesenchymal transition in rat adult male offspring - Sene, Letıćia B. [UNESP]; Rizzi, Victor Hugo GonÇalves [UNESP]; Gontijo, José A. R.; Boer, Patricia A. (The Company of Biologists, 2018)
Studies have shown that adult offspring of mothers fed a protein-restricted diet during pregnancy present a pronounced reduction of nephron number associated with decreased fractional urinary sodium excretion and arterial hypertension. Additionally, recent advances in our understanding of the molecular pathways that govern the association of gestational nutritional restriction, intrauterine growth retardation and inflammation with impaired nephrogenesis, nephron underdosing and kidney fibrosis point to the epithelial to mesenchymal transition (EMT) as a common factor. In the current study, protein and sodium urinary excretion rates were evaluated in rats, and immunohistochemistry and western blot techniques were used to characterize kidney structure changes in 16 week old male offspring of mothers fed a low-protein diet during pregnancy (LP group) compared with age-matched (NP) controls. We also verified the expression of miRNA, mRNA and protein markers of fibrosis and the EMT in whole kidney prepared from LP offspring. We found, surprisingly, that arterial hypertension and long-term hyperfiltration, manifest by proteinuria, were associated with increased renal miR-192 and miR-200 family expression in 16 week old LP relative to age-matched NP rats. Measurement of kidney fibrosis and EMT-related protein markers, by histochemistry and immunoblot techniques, showed a significant rise of TGF-β1 and type-I collagen content in glomeruli and tubulointerstitial areas, accompanied by enhanced fibronectin and ZEB1 and decreased E-cadherin immunoreactivity in 16 week old LP offspring. The results were partially confirmed by increased gene (mRNA) expression of collagen 1α1, collagen 1α2 and ZEB1 in LP whole kidneys compared with those of age-matched NP offspring. In view of the presumed functional overload in the remaining nephrons, we suggest that hypertension and proteinuria development following maternal protein restriction may be a preponderant factor for EMT and structural kidney changes in LP offspring. However, our study was not wholly able to establish the precise role of miRNAs in LP kidney disorders. Thus, further studies will be required to assess the contribution of the miR family to renal injury in a gestational protein-restricted model of fetal programming.
Keywords: Epithelial-to-mesenchymal transition; Fetal programming; Low-protein diet; MiRNA expression; Renal dysfunction